Design and DEM simulation analysis of shaped groove eyelet wheel rapeseed precision seed dispenser - Rao, Gang; Zhao, Wuyun; Shi, Linrong; Chen, Xin; Sun, Bugong; Li, Hui (International Journal of Agricultural and Biological Engineering, 2025)
To address the challenges of low precision and suboptimal seeding efficiency in existing rapeseed seed metering wheels equipped with shaped grooves, the traditional rectangular grooves were redesigned into trapezoidal forms to enhance overall seeding performance. Building upon this modification, a precision metering wheel featuring trapezoidal-shaped grooves capable of dispensing (3±1) seeds per hole was developed, and its fundamental structural parameters were established. Theoretical analysis combined with experimental validation identified four key factors influencing seed filling performance: the inclination angle of the seed guide shaped groove, the rotational speed of the metering wheel, the width of the trapezoidal groove, and the non-standard opening width. A response surface methodology was employed to examine the effects of these factors on the qualification rate, reseeding rate, and missed seeding rate. Results indicated that the qualified seeding rate was 94.17%, the reseeding rate was 3.92%, and the missed seeding rate was 1.91% under optimal parameters. Field tests confirmed that the device met the agronomic requirements for rapeseed sowing. This study serves as a reference for the design of precision sowing devices for rapeseed.Keywords: rapeseed, shaped groove eyelet wheel, response surface methodology, precision sowingDOI: 10.25165/j.ijabe.20251805.9552Citation: Rao G, Zhao W Y, Shi L R, Chen X, Sun B G, Wang Z, et al. Design and DEM simulation analysis of shaped groove eyelet wheel rapeseed precision seed dispenser. Int J Agric & Biol Eng, 2025; 18(5): 102–116.